Conjugated oligomers with alternating heterocycles from a single monomer: synthesis and demonstration of electroluminescence. Issue 21 (25th September 2019) - Urrego-Riveros, Sara; Bremer, Matthias; Hoffmann, Jonas; Heitmann, Anne; Reynaldo, Thibault; Buhl, Janek; Gates, Paul J.; Sönnichsen, Frank D.; Hissler, Muriel; Gerken, Martina; Staubitz, Anne
Abstract : A synthetic strategy for push–pull oligomers is based on a nucleophile and electrophile selective synthesis of the corresponding monomers. Abstract : Conjugated oligomers based on two different heterocycles are typically prepared by step growth polycondensation cross-coupling methods from two monomers X-Cycle 1 -X and M-Cycle 2 -M with no control of the regioselectivity. In this work, we used a new synthetic strategy that involves an extremely chemoselective reaction of a dielectrophilic compound, X 1 -Cycle 1 -X 2, with a dinucleophilic component, M 1 -Cycle 2 -M 2, under Stille conditions. The resulting monomers, X 1 -Cycle 1 -Cycle 2 -M 2 are di-heterocyclic push–pull monomers that still contain a nucleophilic site (boronic acid) and electrophilic site (bromide) and are set up for a controlled polymerization under Suzuki conditions. In this way, two semiconducting oligomers, based on thiophene/benzene and thiophene/pyridine motifs were synthesized. Both oligomers were characterized in terms of their thermal, electrochemical, absorption, emission and electroluminescence properties.